Knowledge, awareness, and prevalence of various types of suturing techniques used for intraoral wound closure - Kethan Umakanth; Mahathi Neralla; Dinesh Prabu (Wolters Kluwer Medknow Publications, 2022)
Wound closing is critical to the completion of any surgical operation. An imperfect closure causes edge isolation, creating a possible route for bacterial contamination, which can lead to infection and scarring. While tissue adhesives and staples are now used as substitutes, surgical sutures remain the gold standard for a safe wound. The aim of this survey is to assess dental students' knowledge on the variety of suturing techniques. A comprehensive online survey of 100 dental students with simple questions about different types of sutures was performed. Each student was asked to complete a questionnaire of 20 questions. This study saw a total of 100 students take part in it. It was found that 58% of the participants opted for interrupted suturing technique and the rest 42% opted for simple continuous technique. It was found that 23% of the participants were not aware of the simple loop suturing technique and the rest 77% were aware of this suturing technique. Thus from the above results and discussion, we will conclude that almost all of the members are fairly privy to the distinctive suturing strategies; however; intensive expertise is required.